§ 1.

  4. f(x)

  g(x) = ( ), :

4.01.

) f(x) = 36 + 2x5 x4 + 3x3 + x 3, g(x) = x 1;
) f(x) = i5 +(i 1)x4 + ix3 + (1 + 2i)x +2, g(x) = x 1 i;

4.02.

) f(x) = 8 2x7 + x6 + 2x5 4x4 + 3x3 x2 + 2x 1, g(x) = x 2;
) f(x) = 6 3x5 +(3 + i)x4 + 3ix3 4ix2 +(4 + 3i)x + i, g(x) = x 1 i;

4.03.

) f(x) = 26 3x4 + 4x2 2x +1, g(x) = x + 2;
) f(x) = 6 2ix5 + (1 i)x4 + 2x3 + ix2 +1, g(x) = x i;

4.04.

) f(x) = 28 x6 3x4 2x +3, g(x) = x + 3;
) f(x) = 6 + ix5 (1 + 2i)x4 + x2 1 3i, g(x) = x 2 + i;

4.05.

) f(x) = 37 x6 + 3x3 2x +5, g(x) = x + 1;
) f(x)=6+(1i)x5+2ix4+(3+3i)x3+x2+(2i1)x2+3i, g(x) = i 1;

4.06.

) f(x) = 25 5x3 3x2 +4, g(x) = x 2;
) f(x) = (1 i)5 ix4+ix3 +(3 5i)x2 +(1 2i)x 4+3i, g(x) = x 1 + i;

4.07.

) f(x) = 47 3x4 + 2x2 3x 3, g(x) = x + 2;
) f(x) = i5+ (1 i)x4 + (2 + i)x3 + ix + 3 i, g(x) = x 1 + i;

4.08.

) f(x) = 25 + 4x4 5x3 + 3x2 2, g(x) = x + 2;
) f(x) = (1 + i)5+ ix4 + (1 2i)x3 + (i 1)x2 9 + 8i, g(x) = x 2 + i;

4.09.

) f(x) = 35 2x4 + x2 5, g(x) = x 4;
) f(x) = i5+ (i 2)x4 + (1 + i)x3 + ix + 4 + i, g(x) = x i;

4.10.

) f(x) = 27 + x5 3x3 + x 4x, g(x) = x + 3;
) f(x) = (3 + i)x6 (2 i)x4 + 3x3 ix2 +3, g(x) = x + 1 2i;

4.11.

) f(x) = 25 + 5x4 2x3 + 2x2 + 5x +20, g(x) = x + 3;
) f(x) = (2 + 3i)x5 2(4 + 5i)x4 15ix3 + (6 + 13i)x2 +  8(3 + 2i)x + 55 + 18i, g(x) = x 3 + 2i;

4.12.

) f(x) = 45 5x3 + 2x2 8x, g(x) = x + 3;
) f(x) = 3x5 ix4 + (2 3i)x3    7x + 1 2i, g(x) = x 1 + 2i;

4.13.

) f(x) = 25 + 2x3 + x2 4x +1, g(x) = x + 2;
) f(x) = ix5 + (2 i)x4 + (2 3i)x3  +  ix2 7 + 2i, g(x) = x 3 2i;

4.14.

) f(x) = 37 + x6 + 2x5 5x4 + x3 + 3x2 7, g(x) = x 1;
) f(x) = ix5 + (1 + 2i)x4 + (1 i)x3  +  ix2 + (1 + i)x +3, g(x) = x 1 + i;

4.15.

) f(x) = 46 3x5 + 2x3 6x2 + x 3, g(x) = x + 3;
) f(x) = ix6 (2 + i)x4 + 3x2    2x 7 + i, g(x) = x 3i;

4.16.

) f(x) = 5 3x4 + 5x3 + 4x2 + 2x 10, g(x) = x 1;
) f(x) = (1 + 2)x5 + (3 + i)x4 + (1 + 2i)x3  (1 + i)x2 + (4 + i)x + 4 + i, g(x) = x 1 i;

4.17.

) f(x) = 25 + 3x4 + 4x3 + x2 1, g(x) = x 1;
) f(x) = x5 + (1 + 2i)x4 (1 + 3i)x2  +7, g(x) = x i;

4.18.

) f(x) = 5 + 2x4 3x3 + 2x2 x 1, g(x) = x 2;
) f(x) = ix5 + ix4 2x3  + x2 + (1 i)x +4, g(x) = x 1 + i;

4.19.

) f(x) = 26 3x4 + 2x3 x2 4x 3, g(x) = x 3;
) f(x) = ix5 +(1 + i)x4 + (5 + i)x3 (1 i)x2 + (3 + i)x + i +5, g(x) = x + 1 i;

4.20.

) f(x) = 26 + 4x3 4x2 + 2x 4, g(x) = x + 1;
) f(x) = x5 + ix4 (1 + i)x2 + 2 + i, g(x) = x 1 + 2i;

4.21.

) f(x) = 36 2x5 x3 4x +1, g(x) = x + 3;
) f(x) = ix5 + (2 + i)x4 3(1 + i)x2 (3 + i)x2 (3 + i)x 2, g(x) = x 1 + i;

4.22.  

) f(x) = 48 3x6 + 2x4 3x3 + 2x 6, g(x) = x + 2;
) f(x) = ix6 (1 + i)x5 + (1 2i)x3 + 2ix2 3(1 i)x +1, g(x) = x 2 i;

4.23.

) f(x) = 28 3x7 + 4x5 x3 + 4x +3, g(x) = x + 4;
) f(x) = ix5 (3 + i)x3 + 2ix2   (4 + 2i)x + 14i, g(x) = x 1 i;

4.24.

) f(x) = 27 3x6 4x3 + 2x2 +3, g(x) = x + 5;
) f(x) = 4x5 + (2 i)x4 5ix3 + (1 + i)x 2i, g(x) = x + 1 i;

4.25.

) f(x) = 37 2x5 + 3x4 2x2 + x 6, g(x) = x 4;
) f(x) = 3ix5 + (3 i)x4 + (4 i)x3 + (1 i)x2 + (2 i)x 2 + 6i, g(x) = x 1 i;

4.26.

) f(x) = 156 8x5 7x4 + x +3, g(x) = x 2;
) f(x) = 2ix5 ix4 +  3x2   ix +1, g(x) = x 1 i;

4.27.

) f(x) = 56 6x5 3x2 2x +1, g(x) = x + 4;
) f(x) = 6x6 5x5   ix3 + (1 + i)x +2, g(x) = x 1 + i;

4.28.

) f(x) = 46 8x5 16x3 + 8x2 + 32x 64, g(x) = x 0,5;
) f(x) = 2x6   ix5 + ix4 + 6x3 + 12x 8 + 2i, g(x) = x + i;

4.29.

) f(x) = 45 6x4 + 5x3 2x +8, g(x) = x + 3;
) f(x) = 4x6 + 6x4 ix3 + (1 i)x2 + 3x 16, g(x) = x 2 i;

4.30.

) f(x) = 37 4x5 + 2x4 6x3 + 2x +11, g(x) = x + 2;
) f(x) = ix6   2x5 + (1 i)x3  3x + 2 3i, g(x) = x + 2i;

4.31.

) f(x) = 27 + 2x6 3x3 + 6x2 7x +10, g(x) = x 4;
) f(x) = 2ix5 ix4 +  3x2 (2 +  3i)x 7 + 2i, g(x) = x 2 +  i;

4.32.

) f(x) = 37 + 8x6 4x4 + 2x2 + 6x +1, g(x) = x + 2;
) f(x) = 2x8   ix7 + 5x5   2ix4 + (1 + i)x2 + 1 2i, g(x) = x 1 + 2i;

4.33.

) f(x) = 646 + 32x3 8x2 72x +8, g(x) = x + 0,5;
) f(x) = 6x5 7x4 + 3x3   (2 + i)x2 3x + 4 3i, g(x) = x + 2 i;

4.34.

) f(x) = 86 4x5 + 3x2 4x +7, g(x) = x + 4;
) f(x) = 2x7   3x6 + (2 i)x4   ix3 (1 + i)x + 3 i, g(x) = x + 3 + i;

4.35.

) f(x) = 28 4x6 + 3x4 2x3 + 7x 12, g(x) = x + 3;
) f(x) = 2x6   (1 + i)x5 ix4   2x2 + 3 3i, g(x) = x 2 + 2i;

4.36.

) f(x) = 47 2x5 + 3x3 4x2 ix + 4 2i, g(x) = x 4;
) f(x) = 2x6 + (1 i)x5 + 2ix4   (3 + 2i)x2 3 + 5i, g(x) = x + 2 2i.

\..\

 

                              Copyright © 2008-2009 ..   . .